Overcoming the entropy of polymer chains by making a plane with terminal groups: a thermoplastic PDMS with a long-range 1D structural order. Issue 9 (11th January 2023) - Chen, Yugen; Ishiwari, Fumitaka; Fukui, Tomoya; Kajitani, Takashi; Liu, Haonan; Liang, Xiaobin; Nakajima, Ken; Tokita, Masatoshi; Fukushima, Takanori
Abstract : Subtle modification, adding methoxy groups to the triptycene termini of a telechelic polydimethylsiloxane (PDMS), dramatically improves mechanical properties, forming a thermoplastic PDMS without the need for covalent cross-linking. Abstract : Due to its unique physical and chemical properties, polydimethylsiloxane (PDMS) is widely used in many applications, in which covalent cross-linking is commonly used to cure the fluidic polymer. The formation of a non-covalent network achieved through the incorporation of terminal groups that exhibit strong intermolecular interactions has also been reported to improve the mechanical properties of PDMS. Through the design of a terminal group capable of two-dimensional (2D) assembly, rather than the generally used multiple hydrogen bonding motifs, we have recently demonstrated an approach for inducing long-range structural ordering of PDMS, resulting in a dramatic change in the polymer from a fluid to a viscous solid. Here we present an even more surprising terminal-group effect: simply replacing a hydrogen with a methoxy group leads to extraordinary enhancement of the mechanical properties, giving rise to a thermoplastic PDMS material without covalent cross-linking. This finding would update the general notion that less polar and smaller terminal groups barely affect polymer properties. Based on a detailed study of the thermal, structural, morphological and rheological properties of the terminal-functionalized PDMS, we revealed that 2D assembly of the terminal groups results in networks of PDMS chains, which are arranged as domains with long-range one-dimensional (1D) periodic order, thereby increasing the storage modulus of the PDMS to exceed its loss modulus. Upon heating, the 1D periodic order is lost at around 120 °C, while the 2D assembly is maintained up to ∼160 °C. The 2D and 1D structures are recovered in sequence upon cooling. Due to the thermally reversible, stepwise structural disruption/formation as well as the lack of covalent cross-linking, the terminal-functionalized PDMS shows thermoplastic behavior and self-healing properties. The terminal group presented herein, which can form a 'plane', might also drive other polymers to assemble into a periodically ordered network structure, thereby allowing for significant modulation of their mechanical properties.